INTEGRASI BUDAYA DAN MATEMATIKA: STUDI ETNOMATIKA PADA KERAWANG GAYO - Maharani, Israq (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
In essence, mathematics originates from the skills involved in various activities within a cultural environment that grows and evolves in society. Therefore, mathematics is influenced by the cultural background of its surroundings. Ethnomathematics is a dynamic representation that can depict the influence of culture on the application of mathematics. Through ethnomathematics, researchers will examine and analyze kerawang gayo as a cultural study of the Gayo Lues highland community in Aceh, relating it to mathematics. This research aims to analyze the mathematical aspects of the kerawang gayo motifs, which are often used in traditional attire, including clothing, scarves, and hats that feature kerawang gayo designs. Based on the identification results, three of the six aspects of ethnomathematics were found, namely aspects of calculation, measurement, and explanation. Additionally, the relationship between ethnomathematics and the kerawang gayo motifs was found to be a potential source for learning mathematics, particularly in the topics of solid geometry, area, and perimeter of plane figures.